Predictors of Different Cigarette Access Behaviours Among Occasional and Regular Smoking Youth - Leatherdale, Scott T. (Can J Public Health, 2005)
BACKGROUND: Understanding the different ways underage youth access tobacco is required in order to develop more effective tobacco access restrictions. The purpose of this study was to examine characteristics that predict whether underage smoking youth buy their own cigarettes, buy their cigarettes from friends, or get someone else to buy their cigarettes. METHODS: Logistic regression analyses were used to examine the predictors of three different tobacco access behaviours among 737 occasional smoking and 2,050 regular smoking youth. RESULTS: Most smoking youth were asked their age less than half of the time when trying to buy cigarettes. Occasional smokers usually buy their cigarettes from a friend (59.5%) and the majority of regular smokers usually buy their own cigarettes (59.8%). Occasional smokers were less likely to buy their own cigarettes (OR 0.85) and more likely to ask someone else to buy their cigarettes (OR 1.24) the more frequently they were asked their age on purchase attempts. Regular smokers were also less likely to buy their own cigarettes (OR 0.70) and more likely to buy their cigarettes from someone else (OR 1.51) or a friend (OR 1.18) the more frequently they were asked their age on purchase attempts. INTERPRETATION: Point-of-sale restrictions are insufficient to prevent youth from acquiring cigarettes because youth commonly access cigarettes from social sources. A more comprehensive approach for restricting access is required that targets both underage youth and individuals who purchase tobacco for underage youth.